PENGARUH PENDIDIKAN AIKA TERHADAP PERILAKU KEAGAMAAN SISWA DI SD MUHAMMADIYAH SEWON BANTUL YOGYAKARTA - Yunita Syafitri; Mahli Zainuddin Tago (Universitas Muhammadiyah Surakarta, 2021)
Humans are creations of Allah who have special features when compared to other creatures. The privilege is determined by his mind and conscience and is constantly growing and developing. Child development is always followed by growth both physically and psychologically. Growth itself means physiological changes as a result of the process of maturing physical functions that take place normally in children supported by environmental factors and the learning process. Religious education is one of the three subject matters that must be included in the curriculum of every formal education institution in Indonesia. The purpose of this study was to determine the effect of learning Islamic religious education on the religious behavior of grade V and VI students at SD Muhammadiyah, to determine the effect of Muhammadiyah education on religious behavior of grade V and VI students at SD Muhammadiyah. as well as knowing the effect of Islamic religious education and Muhammadiyah education simultaneously on the religious behavior of grade V and VI students at SD Muhammadiyah. This type of research is correlational with a quantitative approach. The research sample consisted of 73 students at Muhammadiyah elementary schools in Sewon District, Kab. Bantul Yogyakarta with sampling proportionate stratified random sampling using the Slovin formula. The results of this study indicate that the variables of Islamic religious education and Muhammadiyah education have a positive influence on students' religious behavior. Whereas in the hypothesis test it was concluded that there was an influence between Islamic religious education on students' religious behavior by 16.5%, the effect of Muhammadiyah education on students' religious behavior was 15.2%, the effect of Islamic religious education and Muhammadiyah education on students' religious behavior was 31.7. % and the remaining 68.3% is influenced by other variables outside the model included in this study.